Determination of nutrients and metals content in liquid generated from composted food waste [electronic resource] - Nur Hanismahiza Muda, 1991- author (2015)
Thesis (Sarjana (Kejuruteraan Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2015